73.4k views
3 votes
Solve the system below using substitution write your final answer as a coordinate point

y = -2x + 4
-x + 3y = -9

User Nookaraju
by
5.6k points

1 Answer

5 votes

Answer:

(3, - 2 )

Explanation:

Given the 2 equations

y = - 2x + 4 → (1)

- x + 3y = - 9 → (2)

Substitute y = - 2x + 4 into (2)

- x + 3(- 2x + 4) = - 9 ← distribute and simplify left side

- x - 6x + 12 = - 9

- 7x + 12 = - 9 ( subtract 12 from both sides )

- 7x = - 21 ( divide both sides by - 7 )

x = 3

Substitute x = 3 into (1) for corresponding value of y

y = - 2(3) + 4 = - 6 + 4 = - 2

Solution is (3, - 2 )

User Mzafer
by
5.9k points